2006
DOI: 10.1029/2006gl025812
|View full text |Cite
|
Sign up to set email alerts
|

Seismic anisotropy in the uppermost mantle, back‐arc region of the northeast Japan arc: Petrophysical analyses of Ichinomegata peridotite xenoliths

Abstract: A dense network of seismic stations has been deployed across the northeast Japan arc to investigate mantle wedge structures. To attain independent petrophysical constraints, we determined the seismic properties of Ichinomegata mantle xenoliths from the back‐arc region that were brought to the surface from the mantle lithosphere by volcanic eruptions. We calculated the seismic properties of the xenoliths from olivine and pyroxene crystal‐preferred orientations and single crystal elastic constants. The small mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Olivine crystals have a shape-preferred orientation oblique to the main foliation by 0-30°. Such an oblique foliation is typical of shear deformation and has been reported from rocks of the uppermost mantle of the back-arc region (Ichinomegata peridotite xenoliths, northeast Japan) [Michibayashi et al, 2006]. Hence, from the 16 xenoliths data with each one containing more than 200 measurements, we calculated the average sample (4325 measurements, the sum of all the measurements with respect to the same sense of shear based on each oblique foliation), giving the same weight to each measurement, independently of the number of measurements in each xenolith (Figure 2a).…”
Section: Samples and Methodssupporting
confidence: 54%
“…Olivine crystals have a shape-preferred orientation oblique to the main foliation by 0-30°. Such an oblique foliation is typical of shear deformation and has been reported from rocks of the uppermost mantle of the back-arc region (Ichinomegata peridotite xenoliths, northeast Japan) [Michibayashi et al, 2006]. Hence, from the 16 xenoliths data with each one containing more than 200 measurements, we calculated the average sample (4325 measurements, the sum of all the measurements with respect to the same sense of shear based on each oblique foliation), giving the same weight to each measurement, independently of the number of measurements in each xenolith (Figure 2a).…”
Section: Samples and Methodssupporting
confidence: 54%
“…Although olivine and opx are intrinsically orthorhombic, several studies have demonstrated that crystal aggregates display hexagonal symmetry, rather than purely orthorhombic symmetry [ Mainprice and Silver , 1993; Bystricky et al , 2000; Mehl et al , 2003; Michibayashi et al , 2006]. For example, Bystricky et al [2000] and Michibayashi et al [2006] observe LPO in which olivine a axes are aligned ∼parallel with the shear direction and the b and c axes form a “girdle” perpendicular to the shear direction (i.e., D‐type slip, {0 kl }[100]). In order to simulate hexagonal symmetry using the orthorhombic single‐crystal elastic constants of olivine and opx, the coefficients corresponding to the b and c axes must be combined.…”
Section: Shear Wave Splitting Tomographymentioning
confidence: 99%
“…Our analysis of subgrain boundaries in olivine indicates that the dominant slip system differed between the granular and sheared peridotites, whereas the equilibrium P-T conditions and present water concentrations are nearly identical between the two types. The olivine [100](010) slip system found to be active in the granular peridotite is commonly reported as being active in naturally deformed peridotites from ophiolite complexes (Nicolas and Christensen, 1987) and mantle xenoliths (Avé Lallemant, 1975;Michibayashi et al, 2006), and in laboratory experiments performed at high temperatures under dry conditions (Carter and Avé Lallemant, 1970;Zhang and Karato, 1995). We suggest, therefore, that deformation of the granular peridotites occurred in a hot and dry region in the cratonic root.…”
Section: Differences In Water Contents Estimated Based On Ir and Defomentioning
confidence: 76%